1998
DOI: 10.1002/jpln.1998.3581610110
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between microbial biomass and activity and the soil chemical conditions and the processes of acid load in coniferous forest soils

Abstract: Summary -Zusammenfassung Wechselwirkung der mikrobiellen Biomasse und Aktivitjit mit dem bodenchemischenThe primary aims of the present investigation were to determine the proportion of microbial driven soil processes associated with acidification in coniferous forest soils, and the response of microbial cmmu-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 23 publications
1
7
0
Order By: Relevance
“…In forest ecosystem research the often-used microbial properties have been microbial biomass C or N, and related ratios like respiration to microbial biomass ratio (metabolic quotient) and microbial biomass C to soil organic C. Some of the investigations compared microbial properties along a pH gradient but the investigations were restricted to a single depth or horizon in upper mineral soils (up to 10-cm depth) Domsch 1986, 1993;Wolters and Joergensen 1991;Dilly and Munch 1995;Joergensen et al 1995;Anderson and Joergensen 1997). Other authors looked at microbial properties down the profiles but focused on more and moder type humus profiles only (Scholle et al 1992(Scholle et al , 1993Bauhus and Barthel 1995;Stockfisch et al 1995;Raubuch and Beese 1998;Joergensen and Scheu 1999). At acidic sites, a large part of nutrients available to the plant is located in the thick organic layer and microbial biomass concentration (lg C mic g À1 DW) decreases exponentially from litter layer to mineral soil with depth by factors more than 100 (Scholle et al 1993;Stockfisch et al 1995;Joergensen and Scheu 1999).…”
Section: Introductionmentioning
confidence: 97%
“…In forest ecosystem research the often-used microbial properties have been microbial biomass C or N, and related ratios like respiration to microbial biomass ratio (metabolic quotient) and microbial biomass C to soil organic C. Some of the investigations compared microbial properties along a pH gradient but the investigations were restricted to a single depth or horizon in upper mineral soils (up to 10-cm depth) Domsch 1986, 1993;Wolters and Joergensen 1991;Dilly and Munch 1995;Joergensen et al 1995;Anderson and Joergensen 1997). Other authors looked at microbial properties down the profiles but focused on more and moder type humus profiles only (Scholle et al 1992(Scholle et al , 1993Bauhus and Barthel 1995;Stockfisch et al 1995;Raubuch and Beese 1998;Joergensen and Scheu 1999). At acidic sites, a large part of nutrients available to the plant is located in the thick organic layer and microbial biomass concentration (lg C mic g À1 DW) decreases exponentially from litter layer to mineral soil with depth by factors more than 100 (Scholle et al 1993;Stockfisch et al 1995;Joergensen and Scheu 1999).…”
Section: Introductionmentioning
confidence: 97%
“…Microbial biomass C was determined using the lowest rate of heat production within the first 4 hours after glucose amendment and using the relationship of Sparling (1983): 1 g biomass C mic corresponds to 180.05 mW. From data on microbial biomass and basal heat production the specific activity (heat production per unit biomass mW mg C mic ±1 ) was calculated (Raubuch and Beese, 1998). All given microbial parameters are arithmetic means of the three analyzed replicates and are expressed on an ovendry basis.…”
Section: Methodsmentioning
confidence: 99%
“…Wolters (1991) found that simulated acid rain significantly decreased microbial biomass while specific activity was increased in the Of-layer of a beech moder soil within 132 days. Raubuch and Beese (1998) reported an increase of specific activity in upper mineral soils of naturally acidified coniferous forest soils after 21 months. Bååth and Arnebrant (1994) found that deacidification through liming and wood ash application increased microbial activity and microbial biomass within months and bacterial growth rate within a few years.…”
Section: Summary ± Zusammenfassungmentioning
confidence: 97%
See 1 more Smart Citation
“…Nitrogen fertilization accompanied with tillage yielded highest WEON among all the treatments in both soils. Applying N fertilizer can change microbial community structure (e.g., fungal/bacterial ratio), and subsequently alter organic N mineralization (McDowell et al, 2004;Raubuch and Beese, 1998;Ros et al, 2009). Tillage can break up soil aggregates (Beare et al, 1994;Page et al, 2013) which releases WEON occluded within Table 3 Spectroscopic characteristics of water-extractable organic carbon (WEOC) in the 0-10 cm soil layer as affected by nitrogen fertilization (N) and tillage (T) in a Black Chernozem at Ellerslie and a Gray Luvisol at Breton.…”
Section: Weoc and Weon Responses To N Fertilization And Tillage Revermentioning
confidence: 99%